Analisis daya beli masyarakat melalui Program Kartu Prakerja di era pandemi covid-19 - Rhadityo; Sudiana (FEBI IAIN Langsa, 2022)
The large-scale restriction policy in the Covid-19 Pandemic has caused society activity paralyzed, it caused a serious problem in the economy. The problem occurred such as low peoples’ income resulted in low purchasing power. This study utilized a qualitative descriptive method. The pre-employment card is a bridge that was able to connect people with a variety of new skills training, in addition, the government also hoped to create a society to be more capable and empowered to simultaneously reduce excessive dependence on others. Access facilities to various kinds of tutorial training videos, as well as cash assistance provided by the pre-employment card program. The Pre-employment card program was expected to be able to create jobs, so that, the income increased because of the higher a person’s income, the higher his/her purchasing power and the more diverse needs to be filled, and vice versa. The result in this research affected the low purchasing power during the Covid-19 pandemic cannot be overcome through pre employment allowance due to careless society on trainings in developing skills. The people only accentuated the allowance to directly used effortlessly to add the nominal allowance.